Problems and prospects of the powerloom industry: A study of Champanagar, Bhagalpur city, Bihar - Sonam Kumari; Prashant Kumar (National Geographical Journal of India, 2023)
The industry is crucial to a country's economic prosperity. India has a diverse economy that is growing and thriving in many industries. Similarly, the power loom sector contributes significantly to the economic growth of the rural and urban people in Bhagalpur city. Weavers are a key component of this sector, but they frequently struggle with issues related to their finances, health, and other areas, and they receive little government assistance. As a result, they have extremely low productivity and appalling economic conditions. The Present study is focused on the problems of power loom industries of Champanagar, which explains the economic condition of weavers, their income and living standards. the main aim of the study is to analyze the difficulties regarding the powerloom industry which are faced by the weavers. the study is based on primary data acquired by simple random sampling from weavers. The findings revealed that weavers face several obstacles, including a